2017
DOI: 10.14740/gr886w
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, Endoscopic and Histopathologic Features Among Stool H. pylori Positive and Stool H. pylori Negative Patients With Dyspepsia

Abstract: BackgroundDyspepsia is a common presentation for many patients in gastroenterology clinics. Helicobacter pylori (H. pylori) infection is endemic in many countries around the world and its relation to dyspepsia has long been questioned. This study aimed at comparing demographic, endoscopic and histologic features among dyspeptic patients with and without stool H. pylori antigen positivity.MethodsOne hundred and fifty-one consecutive patients with dyspepsia were divided into group I (n = 80) and group II (n = 71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
2
8
0
1
Order By: Relevance
“…Histopathological examination proved the presence of H. pylori in gastric mucosa of only 77% of infection positive patients, somewhat similar to Mohamed Hasan et al, a study which discovered it histologically in 83.8% of stool antigen-positive [25]. This may be attributed to patchy colonisation of the microorganism.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Histopathological examination proved the presence of H. pylori in gastric mucosa of only 77% of infection positive patients, somewhat similar to Mohamed Hasan et al, a study which discovered it histologically in 83.8% of stool antigen-positive [25]. This may be attributed to patchy colonisation of the microorganism.…”
Section: Discussionsupporting
confidence: 77%
“…The histopathological changes of gastric mucosa, which are the most important axis in this paper, are variable among most studies. In a study of Mohamed Hasan et al, gastritis had been identified histologically in 100% of H. pyloripositive population [25]. Non-atrophic (superficial) gastritis was detected in the majority of H. pyloriinfected individual with no risk of transformation to peptic ulcer or adenocarcinoma [26] while chronic atrophic gastritis is often associated with metaplasia with increased risk of adenocarcinoma [27].…”
Section: Dyspepsiamentioning
confidence: 99%
“…Third, the 98% pathology rate reported in dyspeptic patients. In fact this finding had been reported by one paper from our institution [15] which concluded that all dyspeptic patients had endoscopic and pathologic abnormality even in absence of positive H. pylori testing. When both groups of our study are compared there was a significant difference in chronic gastritis with erosive mucosa in dyspeptic patients than non-dyspeptic patients which emphasizes the findings of Emara et al, 2017 [15] who found pathologic gastric mucosa in all patients with dyspepsia, probably due to inclusion of patients from the same locality.…”
Section: Discussionsupporting
confidence: 74%
“…However, Egypt had high prevalence rates of infection that approaches 70% -90% in elderly population [14]. We usually rely on non-invasive use of H. pylori antigen in stool in daily medical practice [15].…”
Section: Discussionmentioning
confidence: 99%
“…H pylori infection: is defined in this study when the patient was positive or negative for H pylori antigen in stool provided that he did not receive any PPI or antibiotics in the last 4 weeks prior to the examination. [15,16]…”
Section: Methodsmentioning
confidence: 99%